2021
DOI: 10.1186/s12885-021-08352-z
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors do not affect overall survival in soft tissue sarcoma when patients treated at a single high-volume center

Abstract: Background Treatments for soft tissue sarcoma (STS) include extensive surgical resection, radiation and chemotherapy, and can necessitate specialized care and excellent social support. Studies have demonstrated that socioeconomic factors, such as income, marital status, urban/rural residence, and educational attainment as well as treatment at high-volume institution may be associated with overall survival (OS) in STS. Methods In order to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our results complete and shed new light on another study observing no association between social deprivation and the survival of soft-tissue sarcoma patients conducted in the specific setting of a retrospective analysis in the single high-volume University of Washington Medical Center. According to this results, Eastman et al suggest that “treatment at a high volume institution may mitigate the importance of socio-economic factors in the overall survival of soft-tissue sarcomas” [ 44 ]. Mandatory referral of all patients to reference centers is interesting to reduce inequalities in cancer management and survival, but here we found that such results can also be achieved through a more flexible organization driven by a reference network, following the model of hub and spoke, and which can help to avoid some potential adverse effects for patients related to the variable spatial accessibility of these reference centers [ 22 ] and the cumulative impact of long journeys on quality of life [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results complete and shed new light on another study observing no association between social deprivation and the survival of soft-tissue sarcoma patients conducted in the specific setting of a retrospective analysis in the single high-volume University of Washington Medical Center. According to this results, Eastman et al suggest that “treatment at a high volume institution may mitigate the importance of socio-economic factors in the overall survival of soft-tissue sarcomas” [ 44 ]. Mandatory referral of all patients to reference centers is interesting to reduce inequalities in cancer management and survival, but here we found that such results can also be achieved through a more flexible organization driven by a reference network, following the model of hub and spoke, and which can help to avoid some potential adverse effects for patients related to the variable spatial accessibility of these reference centers [ 22 ] and the cumulative impact of long journeys on quality of life [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The portability of pathology and imaging results without a requirement for patient travel has the promise of revolutionizing care structures for rare cancers. Treatment at a referral center has been shown to normalize oncologic outcomes regardless of socioeconomic status, 24 and the goal would be that by maintaining the flow of communication and taking advantage of emerging technologies, all sarcoma patients regardless of location will have access to multidisciplinary sarcoma care.…”
Section: Discussionmentioning
confidence: 99%
“…17 In fact, different studies have shown better survival in sarcoma patients managed by expert centres. [18][19][20][21] Thus, it is imperative that the countries following the centre-based model, where there are no collaboration mechanisms between expert and non-expert centres, facilitate patients' access to RCs. Lithuania, with 3 million inhabitants and two RCs, implemented a system to capture the patients who need their services.…”
Section: Discussionmentioning
confidence: 99%